High‐temperature flexural strength of SiC ceramics prepared by additive manufacturing. Issue 2 (3rd January 2020) - Xu, Teng‐Teng; Cheng, Su; Jin, Lai‐Zhen; Zhang, Kun; Zeng, Tao
Abstract: Silicon carbide (SiC) ceramics, as a kind of candidate material for aero‐engine, its high‐temperature performance is a critical factor to determine its applicability. This investigation focuses on studying the high‐temperature properties of SiC ceramics fabricated by using additive manufacturing technology. In this paper, SiC ceramics were prepared by combining selective laser sintering (SLS) with precursor infiltration and pyrolysis (PIP) technique. The microstructure, phase evolution, and failure mechanism after high‐temperature tests were explored. SiC ceramic samples tested at room temperature (RT), 800°C, 1200°C, 1400°C, and 1600°C demonstrated bending strengths of 220.0, 226.1, 234.9, 215.5, and 203.7 MPa, respectively. The RT strength of this material can be maintained at 1400°C, but it decreased at 1600°C. The strength retention at 1400°C and 1600°C were 98% and 92%, respectively. The results indicate that the mechanical properties of SiC ceramics prepared using this method have excellent stability. As the temperature increases, the bending strength of the specimens increased slightly and reached the peak value at 1200°C, and dropped to 203.7 MPa at 1600°C. Such an evolution could be mainly due to the crack healing, and the softening of the glassy phase.